Volunteerism in support of Abkhazia 1992–1993, and the process of ethnogenesis Abkhazians - A. I. Broido (Vestnik MGIMO-Universiteta)
Статья посвящена трагическим событиям грузино-абхазского вооруженного противостояния 1992-1993 годов и их предыстории. Автором исследована и отмечена значительная роль добровольцев, в большинстве своем бескорыстно и самоотверженно воевавших в рядах абхазской армии и способствовавших ее успехам. Summary. The article is devoted to the tragic events of Georgian-Abkhaz armed conflict 1992-1993, and their background. The author researched and noted the significant role of volunteers, mostly selflessly and devotedly fought in the ranks of the Abkhaz army and contributed to its success.